Polyoxometalate/Polyethylene Glycol Interactions in Water: From Nanoassemblies in Water to Crystal Formation by Electrostatic Screening. Issue 35 (11th April 2017) - Buchecker, Thomas; Le Goff, Xavier; Naskar, Bappaditya; Pfitzner, Arno; Diat, Olivier; Bauduin, Pierre
Abstract: In the last decade organic–inorganic hybrid materials have become essential in materials science as they combine properties of both building blocks. Nowadays the main routes for their synthesis involve electrostatic coupling, covalent grafting, and/or solvent effects. In this field, polyoxometalates (POMs) have emerged as interesting inorganic functional building blocks due to their outstanding properties. In the present work the well‐known α‐Keggin polyoxometalate, α‐PW12 O40 3− (PW), is shown to form hybrid crystalline materials with industrial (neutral) polyethylene glycol oligomers (PEG) under mild conditions, that is, in aqueous medium and at room temperature. The formation of these materials originates from the spontaneous self‐assembly of PW with EO x, (EO=ethylene oxide) with at least four EO units ( x >4). The PW–PEG nanoassemblies, made of a POM surrounded by about two PEG oligomers, are stabilized by electrostatic repulsions between the negatively charged PW anions. Addition of NaCl, aimed at screening the inter‐nanoassembly repulsions, induces aggregation and formation of hybrid crystalline materials. Single‐crystal analysis showed a high selectivity of PW towards EO5 –EO6 oligomers from PEG200, which is made of a mixture of EO3–8 . Therefore, a general "soft" route to produce POM–organic composites is proposed here through the control of electrostatic repulsions between spontaneously formed nanoassemblies in water. However, this rational design of new POM hybrid (crystalline) materials with hydrophilic blocks, using such a simple mixing procedure of the components, requires a deep understanding of the molecular interactions. Abstract : Come together : The screening of the electrostatic repulsions between spontaneously formed ethylene glycol‐polyoxometalate nanoassemblies promotes the formation of a crystalline hybrid material.